Intercultural Competence: Is It One of the Goals of English Language Teaching in Serbia? - Vera V. Ošmjansk; Lidija V. Beko (University of Belgrade, Teacher Education Faculty, 2019)
The paper presents our research aimed at determining students' and university level English language teachers' attitudes towards developing intercultural competencies within the framework of English language teaching and learning. Two questionnaires were used as instruments in the quantitative research, while the obtained data were analysed by means of descriptive linguistics, χ2 test (Chi-squared test) and the Independent Sample t-Test. The results confirm the research hypothesis that the concept of teaching only the culture of Anglophone countries in English language instruction is indeed prevalent among the English language experts - teachers and students at several Departments of English Language and Literature in Serbia. On the other hand, the results are indicative of a generally positive shift in terms of the need for including other cultures, as well as the repondents' readiness to use situations and texts related to Serbian culture in their English classes. Our conclusion is that a good starting point for innovations is developing in the field of English language teaching. These innovations refer to the adoption of attitudes in favour of acquiring intercultural competencies.